2015
DOI: 10.1063/1.4906234
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of selectivity mechanisms in molecular transport through channels and nanopores

Abstract: Selectivity is one of the most fundamental concepts in natural sciences, and it is also critically important in various technological, industrial and medical applications. Although there are many experimental methods that allow to separate molecules, frequently they are expensive and not efficient. Recently, a new method of separation of chemical mixtures based on utilization of channels and nanopores has been proposed and successfully tested in several systems. However, mechanisms of selectivity in the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…5,6 Diffusion of the fluid in various nanogeometries is of great interest because of various applications, such as molecular sensing, 7-11 controlled drug delivery, 12,13 and nanofiltration. [14][15][16][17] Recent studies suggest that the transport properties of fluid in confined nanogeometries show anisotropic behavior. [18][19][20][21][22] The self-diffusivity of fluids confined in various nanogeometries, such as slit shaped nano-pores, [23][24][25][26] cylindrical nanotube, 27,28 and carbon nanotube [29][30][31][32][33] have been widely investigated using molecular dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Diffusion of the fluid in various nanogeometries is of great interest because of various applications, such as molecular sensing, 7-11 controlled drug delivery, 12,13 and nanofiltration. [14][15][16][17] Recent studies suggest that the transport properties of fluid in confined nanogeometries show anisotropic behavior. [18][19][20][21][22] The self-diffusivity of fluids confined in various nanogeometries, such as slit shaped nano-pores, [23][24][25][26] cylindrical nanotube, 27,28 and carbon nanotube [29][30][31][32][33] have been widely investigated using molecular dynamics simulation.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive theoretical framework for investigation of chemical mechanisms of translocation and selectivity under stationary-state conditions was recently developed based on this discrete-state kinetic approach. 6,8,10 Importantly, it was also shown that both theoretical methods are mathematically equivalent. 6,8 Recently, stochastic gating has been investigated theoretically using the continuum diffusion description.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The importance of translocation through pores stimulated extensive theoretical studies to uncover the underlying molecular mechanisms. [3][4][5][6][7][8][9][10][11][12] But many questions remain open. Specifically, most of existing theoretical studies of channel-facilitated molecular transport concentrate on investigating systems, where interactions between particles and the channel are constant over the time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chemical kinetics, reaction profiles have long been used to qualitatively rationalise the outcomes of chemical reactions, casting light upon preferred mechanisms and the effects of catalysis [1,2]. In biology, energy landscapes are central to understanding the microscopic origins of processes, including protein folding [3,4,5,6,7,8] and selective transport through membrane channels [9,10,11,12,13,14]. Elucidating the factors governing the dynamics of stochastic processes may be central to even more diverse problems, such as understanding electron transport [15] or the changing stock prices in financial markets [16,17,18].…”
mentioning
confidence: 99%